Refocusing cancer multidisciplinary team meetings in the United Kingdom: comparing urology with other specialties - Warner, R (Ann R Coll Surg Engl, 2021)
INTRODUCTION: Multidisciplinary team (MDT) meetings have been the gold standard of cancer care in the UK since the 1990s. We aimed to identify the views of urology cancer MDT members in the UK on improving the functioning of meetings and compare them with those of other specialties to manage the increasing demand on healthcare resources and enhance the care of complex cancer cases. METHODS: We analysed data from 2 national surveys distributed by Cancer Research UK focusing on the views of 2,294 and 1,258 MDT members about cancer MDT meetings. FINDINGS: Most breast, colorectal, lung and urology cancer MDT members felt meetings could be improved in the following areas: time for meeting preparation in job plans, streamlining of patients, auditing meeting decisions and prioritising complex cases. Most urology respondents (87%) agreed some patients could be managed outside a full MDT discussion, but this was lower for other specialties (lung 78%, breast 75%, colorectal 64%). CONCLUSIONS: To facilitate decisions on which patients require discussion in an MDT meeting, factors adding to case complexity across all tumour types were identified, including rare tumour type, cognitive impairment and previous treatment failure. This study confirms that urology MDT members are supportive of changing from reviewing all new cancer diagnoses to discussing complex cases but managing others with a more protocolised pathway. The mechanisms for how to do this and how to ensure the safety of patients require further clarification.